2011
DOI: 10.4061/2011/561548
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-Related EBV-Associated Smooth Muscle Tumors: A Review of 64 Published Cases

Abstract: The number of reported cases of smooth muscle tumor (SMT) arising in patients with AIDS has been increasing since the mid-1990s. The aim of this study is to characterize the epidemiology, clinical manifestations, pathologic features, prognosis and, management of Epstein-Barr virus-related SMT (EBV-SMT) in patients with AIDS. An English language literature search identified 53 articles including 64 reported cases of EBV-SMT. The majority of these reports involved patients who were young, severely immunosuppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(161 citation statements)
references
References 55 publications
9
142
0
2
Order By: Relevance
“…82 Although these tumors were originally divided into EBV-associated leiomyomas and leiomyosarcomas, current classification holds them all collectively as smooth muscle tumors as they are usually indolent although somewhat unpredictable in behavior. True metastatic behavior is rare, and was observed only in 4 of 51 AIDS-associated (8%) 77 and 1 of 19 cases (5%) in a mixed AIDS and transplantation-associated series. 85 Based on a large survey of AIDS-associated cases, mitotic rate does not seem to distinguish cases with malignant outcome.…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 98%
See 2 more Smart Citations
“…82 Although these tumors were originally divided into EBV-associated leiomyomas and leiomyosarcomas, current classification holds them all collectively as smooth muscle tumors as they are usually indolent although somewhat unpredictable in behavior. True metastatic behavior is rare, and was observed only in 4 of 51 AIDS-associated (8%) 77 and 1 of 19 cases (5%) in a mixed AIDS and transplantation-associated series. 85 Based on a large survey of AIDS-associated cases, mitotic rate does not seem to distinguish cases with malignant outcome.…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 98%
“…The smooth muscle tumors can occur in peripheral soft tissue, intracranial space, or visceral sites, and tumor multiplicity is common. [76][77][78][79][80][81][82][83][84][85] Molecular genetic analysis has shown that multiple tumor represent independent clones rather than dissemination of a single neoplastic clone. 85 In multiple tumor cases, tumors arising in the transplant are of donor cell origin, whereas those at the other sites arise from recipient cells, which also points to polyclonal origin of multiple tumors.…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar mechanism was proposed for EBV-SMT, except CD21 receptors are not detected on smooth muscle cells. Fusion of smooth muscle cells with an infected B-lymphocyte prior to tumor proliferation has therefore been postulated (12). EBV has two strains (types 1 and 2) with different biological behavior, which are distinguished by polymorphisms in EBNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recientemente se ha descrito el rol de este virus en la etiología de múltiples tumores de musculo liso que ocurren en pacientes jóvenes con SIDA, en varias localizaciones del cuerpo (23) . El comportamiento de estos tumores no es siempre agresivo, aunque pueden llegar a ser muy sintomáticos dependiendo de su localización, en especial cuando afectan el sistema nervioso central.…”
Section: Virus Epstein Barrunclassified